Enhancement in Thermoelectric Properties of Cubic Ge2Sb2Te5Thin Films by Introducing Structural Disorder - Manish Kumar (2018)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Thermoelectric performances are usually enhanced by minimizing the thermal conductivity of materials, either by introducing superlattice structures or nanostructuring. Here, a new approach to performance enhancement, based on Seebeck coefficient improvement, is presented for Ge2Sb2Te5thin films. The electron temperature was controlled by using pulsed direct current (DC) plasma power, and the resulting structural disorder of the cubic crystalline phase enhanced the Seebeck coefficients, as supported by molecular orbital calculations. Our results demonstrate a room-temperature Seebeck coefficient of 190.8μVK-1for 200nm films deposited on glass. That′s a disorder! Here, a new approach to thermoelectric performance enhancement, based on Seebeck coefficient improvement, is presented for Ge2Sb2Te5thin films. The electron temperature was controlled by using pulsed direct current (DC) plasma power, and the resulting structural disorder of the cubic crystalline phase enhanced the Seebeck coefficients, as supported by molecular orbital calculations. Our results demonstrate a room-temperature Seebeck coefficient of 190.8μVK-1for 200nm films deposited on glass.